'Prolonger une image ou une danse': Denis's and Breillat's nightclubs. Issue 1 (2nd January 2021) - Grace, Michael
ABSTRACT: Claire Denis's and Catherine Breillat's films pass through nightclubs with striking frequency. Though their work emerges with the rise of clubbing in the 1970s and 80s, their liminal clubs bear a skewed relation to the representation of geographically rooted subcultures. A place rather of transient fantasy, they allow marginal bodies into the light and those usually in focus to move differently, if only for a moment. This article thus asks how we might understand the queerness of the space in films with little room for overt queer politics. Drawing on queer theoretical turns to the potentiality of ephemera, I show how club aesthetics reflect differently on broader issues of antecedence and immediacy in film-phenomenology. Unlike the enduring, up-close explorations of the French cinema of sensation more broadly, the club's stroboscopic aesthetic offers fleeting images emerging and receding swiftly beyond perception. Finding not identifiable queer representation or its absolute, 'fluid' dissolution as is often risked in clubbing discourse and some 'postmodern' interpretations of queer theory, I suggest that Denis's and Breillat's clubs foster attentiveness to different, impermanent and indeterminate kinds of evidence. This makes room for a body and its history without foreclosing the promise of others.